THE INFLUENCE OF EMOTIONAL INTELLIGENCE ON EMPLOYEE PERFORMANCE MEDIATED BY COOPERATIVE CONFLICT MANAGEMENT STYLE OF INTEGRATING AND COMPROMISING - Noermijati, Noermijati; Sunaryo, Sunaryo; Ratri, Indah Kurnia (Universitas Brawijaya, Indonesia, 2019)
This study aimed to analyze the relationship between emotional intelligence, conflict management styles, and employee performance at P4TK PKn IPS office in Batu, East Java. The population of this study is 100 civil servant employees with a minimum length of service of one year and the minimum rank of 5. The whole population is used as the sample (saturated sample), and the data were analysed using smartPLS 3.0. The result of this study shows that emotional intelligence significantly influences integrating style, compromising style, and employee performance. Also, integrating style has a significant influence on employee performance. This study also confirms that integrating style partially mediates the influence of emotional intelligence on employee performance. Finally, this study confirms that emotional intelligence in public organizations can provide benefits that are found in private organizations. Because this study focuses only on integrating and compromising styles, subsequent research can investigate the less cooperative conflict management styles such as bonding, dominating, and avoiding and comparing the three styles with integrating and compromising style. Therefore, next researches can determine whether or not emotionally intelligent employees avoid the use of the less cooperative conflict management styles and determine the influence of the styles on performance.